The association between body roundness index and handgrip strength and muscle quality index: A cross-sectional study. - Zhihao Wei; Tengfei Yu; Xufeng Jin; Guanyi Ma; Xianfeng Meng (PLoS ONE)
Background Sarcopenic obesity is characterized by a combination of obesity and sarcopenia. Body round index (BRI) is a novel anthropometric index that can more accurately assess body and visceral fat levels than body mass index or waist circumference. This study used data from the National Health and Nutrition Examination Survey (NHANES) to explore the relationship between BRI and handgrip strength (HGS) and muscle quality index (MQI) in American adults aged 20 and over. Methods This study used cross-sectional data from the 2011-2014 National Health and Nutrition Examination Survey (NHANES) with complete data on BRI, HGS, and MQI. We used multivariate linear regression models and smooth curve fitting methods to explore the relationship between BRI and HGS and MQI. In addition, subgroup analyses and interaction tests were performed to further analyze the potential association between these variables. Results A total of 5466 participants were finally included in this study, of whom 2807 were males and 2659 were females. The results showed that BRI was positively correlated with HGS and negatively correlated with MQI. In the fully adjusted model, the negative correlation between BRI and MQI was (β= -0.08, 95% CI = -0.08, -0.07), while the positive correlation with HGS was (β= 0.3 8, 95% CI = 0.29, 0.46), indicating that for every unit increase in BRI, MQI decreases by 0.08 units and HGS increases by 0.38 units (P < 0.0001). In addition, the relationship between BRI and HGS is an L-shaped curve. An inflection point is determined when BRI reaches 3.42. Before this threshold, for every unit increase in BRI, HGS increases significantly (β = 2.19, 95% CI = 1.66, 2.72). Conclusion The results showed that BRI was positively correlated with HGS and negatively correlated with MQI, meaning that higher BRI was associated with higher HGS and lower MQI. This highlights the importance of body fat distribution in muscle health and suggests that BRI can be used as an effective anthropometric indicator to predict grip strength and muscle mass.